Nuevas narrativas híbridas como género periodístico en plataformas digitales - Avegno Urquiza, Rommy Jeomira (2021)
This investigative work shows the new narratives that have been developed with technological advances, changes in journalistic work and how they have created or innovated the way in which the events that occurred are narrated, these narratives that due to their great scope and use, are could begin to be classified as journalistic genres, likewise, these present new or improved ways of sharing journalistic content so that the user can be fully informed, since their objective is for the user to feel that he was in the place of the events so that so you can draw your own conclusions, creating a whole experience, instead of just reporting. This project was carried out through observation files to learn about the journalist genres or the new narratives used by the international, national and provincial digital media, consequently, it would also be analyzed what elements they use to tell the story of their multimedia reports, articles, reports, specials, among others. On the other hand, communication professionals were interviewed to study what genres they use in their digital media, the differences between working for a traditional or digital medium and the changes in the profile of the current communicator. In this way, the variety of resources that journalists are now using, digital platforms, as well as the team they form and everything that goes into creating a digital journalistic product would be explored.